1997
DOI: 10.3109/13682829709021453
|View full text |Cite
|
Sign up to set email alerts
|

Historical issues in intervention research: Hidden knowledge and facilitating techniques in Denmark

Abstract: S Facilitating techniques have recently both gained wider popularity and stirred considerable controversy. They are usually assumed to originate in Australia but the present paper documents that similar techniques created a major public event in Denmark and appeared occasionally in the USA in the 1960s and 1970s. However, in spite of the dramatic claims made by proponents of the techniques, their use did not spread widely and the international network has remained tenuous. It is argued that the ‘discovery’ of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It has been used extensively in Australia and in the USA, and is employed in a small number of centres in the UK. Research has shown that the meanings produced via Facilitated Communication are likely to be projected by the facilitator (Datlow-Smith et al 1994;Von Tetzchner, 1997). Bunning (1995) states 'reported evidence of facilitator influence demonstrates the risk to ownership of the communication act, and may even be viewed as an infringement of civil and personal rights'.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used extensively in Australia and in the USA, and is employed in a small number of centres in the UK. Research has shown that the meanings produced via Facilitated Communication are likely to be projected by the facilitator (Datlow-Smith et al 1994;Von Tetzchner, 1997). Bunning (1995) states 'reported evidence of facilitator influence demonstrates the risk to ownership of the communication act, and may even be viewed as an infringement of civil and personal rights'.…”
Section: Introductionmentioning
confidence: 99%
“…The first published descriptions of ''hidden knowledge'' appeared in Denmark in the 1960s, including descriptions of accusations of sexual abuse made with facilitated communication (von Tetzchner, 1997), but the events in Denmark had less influence internationally than the publications of Rosemary Crossley and Douglas Biklen in the 1980s and 1990s (e.g., Biklen, 1990Crossley, 1988Crossley, , 1994Crossley & Remington-Gurney, 1992).…”
mentioning
confidence: 99%
“…Rather, we were tapping language that was already present'' (Crossley & Remington-Gurney, 1992, p. 37). However, a considerable number of experimental studies have failed to substantiate the claims of hidden knowledge and have instead demonstrated that it is the facilitators who produce the messages (for reviews, see, for example, Bober, 2010;Cummins & Prior, 1992;Green, 1994;Jacobson, Foxx, & Mulick, 2005;Mostert, 2001Mostert, , 2010Probst, 2005;Sénéchal, Larivée, & Richard, 2004;von Tetzchner, 1996von Tetzchner, , 1997.…”
mentioning
confidence: 99%